Targeted Synthesis of Anthranilic Diamides Insecticides Containing Trifluoroethoxyl Phenylpyrazole - Li, Huangong; Zhao, Yangyang; Sun, Pengwei; Gao, Li; Xiong, Lixia; Yang, Na; Zhou, Sha; Li, Yuxin; Li, Zhengming (Chemical research in Chinese universities, 2021)
A series of novel anthranilic diamides analogues( 9 a– 9 t) containing trifluoroethoxyl pyrazole moiety was designed and synthesized and their insecticidal bioactivities against Mythimna separata (Walker, M. separata ) and Plutellaxylostella ( P. xylostella ) were evaluated. The structures of the title compounds were confirmed by 1 H NMR, 13 C NMR and HRMS. Preliminary insecticidal activities showed that some of the title compounds possessed good to excellent bioactivities towards M. separata and P. xylostella . Compounds 9 c and 9 t exhibited 100% mortality rate against M. separate at 0.2 mg/L. For the P. xylostella , the synthesized compounds( 9 c– 9 e, 9 i and 9 o) showed 70%, 80%, 75 %, 65% and 60% insecticidal activities at 1×10 −6 mg/L, respectively, higher than that of chlorantraniliprole(0). Based on excellent insecticidal activities, the mode of the action was tested by the calcium-imaging technique, the results of which demonstrated that the novel compounds shared the same target with chlorantraniliprole. The binding pose of the most active compound 9 t in RyRs of P. xylostella was predicted by molecular docking, which showed that compound 9 t interacted with the residues Glu140(A) and His147(A) via hydrogen bond.